Hospitalizations for cancer in international migrants versus local population in Chile - Marcela Oyarte; Iris Delgado; Víctor Pedrero; Lorenzo Agar; Báltica Cabieses (Universidade de São Paulo, 2018)
ABSTRACT OBJECTIVE To compare cancer hospital morbidity among the local population and the immigrant population in Chile. METHODS This is a prevalence study based on the analysis of hospital discharges of all the health centers of Chile. Cancer hospital discharges were characterized in 2012 according to the migratory status. The crude and specific rates of hospital morbidity for this cause were estimated for the analysis of their association with migratory status using zero-inflated negative binomial regression, adjusted for sociodemographic variables. RESULTS The neoplasms were the third cause of hospital discharges for immigrants and the seventh one for Chileans. The adjusted rate of cancer hospital discharges was higher for Chileans than immigrants, and the latter had fewer days of hospitalization and greater proportion of surgical interventions. In the group of immigrants, cancer hospital discharges mainly corresponded to patients belonging to the private system (46%), and in the group of Chileans they mainly corresponded to patients in the public system (71.1%). We observed a large difference in the proportion of cancer hospital discharges for patients with no health insurance between the two populations (22.6%: immigrants, 1.0%: Chileans). In both populations, the three most frequent types of cancer were: (i) lymphoid tissue, hematopoietic organs, and related tissues, (ii) digestive organs, and (iii) breast cancer. CONCLUSIONS Models of differentiated care should be considered for immigrants, with the creation of specific programs of information, coverage, and protection against cancer. More information on this problem must be generated at the local and international level.